Teachers’ Professional Competence, School Climate, and Student Achievement: A Quantitative Study of Indonesian Public Senior High Schools - Yusnita Yusnita; Tri Widayatsih; Muhammad Fahmi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study examines the effect of teacher professional competence and school climate on student achievement in public senior high schools. A quantitative, cross-sectional survey design was employed with a sample of 152 respondents (100 students and 52 teachers) selected through proportionate stratified random sampling from three public senior high schools in Sungai Lilin District, South Sumatra, Indonesia. Data were collected using validated questionnaires (90 items, 5-point Likert scale) and analyzed using simple and multiple linear regression. Findings indicate that: (1) teacher professional competence has a significant positive effect on student achievement (β = 0.569, p < 0.001); (2) school climate also significantly affects student achievement (β = 0.219, p < 0.001); and (3) jointly, both variables explain 56.4% of the variance in student achievement (F = 34.015, p < 0.001, R² = 0.564). These results underscore the importance of investing in teacher professional development and fostering a positive school climate to enhance academic outcomes. However, the cross-sectional design precludes causal inference, and generalizability is limited to similar Indonesian rural-adjacent contexts. Future research should employ longitudinal designs and include objective achievement measures beyond self-reported perceptions.